2018
DOI: 10.1111/jfpe.12919
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of water and energy use at process level in the U.S. beef packing industry: Case study in a typical U.S. large‐size plant

Abstract: Food processing industries consume intensive water and energy to produce food products. However, their water and energy data are scarce and require for good measurement approaches. This study presents data collection and analysis of process‐level water and energy use in a large‐size U.S. beef packing plant through a combined use of portable and in‐line meters and theoretical calculations. The kill floor and plant cleaning are the primary water users, accounting for 28.7 and 24.0%, respectively. The refrigerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…An American beef packaging plant has taken as an example to estimate the amount of water and energy consumed during its beef processing. The results showed that the slaughtering and cleaning processes consumed the most amount of water, and the refrigeration compressor system consumed the most energy [17].…”
Section: Internal Research Of the Wef Nexusmentioning
confidence: 99%
“…An American beef packaging plant has taken as an example to estimate the amount of water and energy consumed during its beef processing. The results showed that the slaughtering and cleaning processes consumed the most amount of water, and the refrigeration compressor system consumed the most energy [17].…”
Section: Internal Research Of the Wef Nexusmentioning
confidence: 99%
“…The high rates of electrical energy and natural gas consumption are associated with the refrigeration and freezing of produced meat and with the heating of water for meat processing. 125 A combination of waste heat from plant operations and biofuels produced in the treatment of wastewater could improve the economic viability of different treatment options.…”
Section: Resource Recoverymentioning
confidence: 99%
“…The process-specific data (e.g., resource inputs and waste outputs in Fig. 1) are collected from the two commercial US beef processing plants located in the Midwest (Li et al, 2019a(Li et al, , 2018bZiara et al, 2018). Those data are further normalized based on the functional unit (1000 kg of live-cattle weight) and processed as the technology matrix coefficient for the process-based system.…”
Section: Life Cycle Inventory Analysismentioning
confidence: 99%
“…Therefore, assumptions are made to describe parametric probability distributions of those four uncertainty sources based on available data and literature. For AP (technology coefficient), triangular distribution with 70%, 130% of process-specific data (e.g., m 3 /1000 kg LCW, kWh/1000 kg LCW) was assigned as the lower and upper limits, respectively, based on the coefficients of variation in onsite data via one-year data collection (Li et al, 2018b). For uncertainty in EP (direct environmental emissions per physical unit), it is assumed to follow a lognormal distribution with 10% of mean values as one standard deviation based on precalculations of environmental impacts per unit under the default uncertainty information within the ecoinvent 3.3 (Ciroth et al, 2016).…”
Section: Uncertainty and Sensitivity Analysismentioning
confidence: 99%